The role of institutional factors in the development and consolidation of inclusive businesses with small farmers at the base of the pyramid - Maestre Matos, Leydis Marcela; Lombana Coy, Jahir; Mesías Díaz, Francisco Javier; Páez Cabas, Andrea Paola (REVESCO. Revista de Estudios Cooperativos, 2023)
Inclusive businesses are ventures that have at the base of the pyramid (BoP) a link that generates economic and social value for the supply chain. Its development requires the identification of formal institutional factors to create and strengthen the BoP in countries with high levels of poverty. The objective of this research is to identify these factors through the case study of six cooperatives that produce export bananas in Colombia, whose BoP are small producers. The methodology combines the collection and analysis of quantitative information that is evaluated through a model of structural equations and is verified with the collection and qualitative analysis of interviews. Among the results, the importance of factors such as the social responsibility policies of anchor companies and the compliance with standards and certifications by small agricultural producers stand out. The training support to the BoP is also noteworthy, thanks to the financial and non-financial assistance provided by various actors in the value chain.
Keywords: Cooperatives; Banana; Colombia; Formal institutions